Systematic risk factors for Australian stock market returns: a cointegration analysis - Mazharul H. Kazi (Australasian Accounting, Business and Finance Journal, 2008)
This paper identifies the systematic risk factors for the Australian stock market by applying the cointegration technique of Johansen. In conformity with the finance literature and investors’ common intuition, relevant a priori variables are chosen to proxy for Australian systematic risk factors. The results show that only a few systematic risk factors are dominant for Australian stock market price movements in the long-run while short-run dynamics are in place. It is observed that the linear combination of all a priori variables is cointegrated although not all variables are significantly influential. The findings show that bank interest rate, corporate profitability, dividend yield, industrial production and, to a lesser extent, global market movements are significantly influencing the Australian stock market returns in the long-run; while in the short-run it is being adjusted each quarter by its own performance, interest rate and global stock market movements of previous quarter.
Keywords: Systematic risk factors; returns; APT; Johansen; Australian stock market